Examining the Impact of Formal and Informal Learning On the Creativity of Women Inventors - Jamie L. McCracken (Adult Education Research Conference, 1998)
This research is about women inventors and how they feel education impacted their creativity. Data gathered strongly supports existing data which theorizes that "women's learning" (e.g. connected learning and relational learning) is different from men's. Creative women speak out about how they felt education impacted their creativity and what they would like to see education do to increase creativity and self-esteem in girls and women.